Protected, Yet Undocumented: The U.S. Case of Growing Liminal Immigration Status and the Theoretical, Advocacy, and Policy Implications for the U.S. and Beyond - Connor, Phillip (The International migration review, 2024)
Often, undocumented immigrants are considered a population living in the shadows. But living below the radar of U.S. governmental authorities is no longer as accurate. As of the end of 2023, estimates indicate nearly six million, or nearly half, of the undocumented population has some level of liminal or protected status. At the same time, these protections are more temporary than before as most immigration policy now occurs in the executive, and not the legislative, branch, and is subject to dramatic shifts with a change in administration. Also, the diversity of protection types has grown. Using data for the U.S. case, this paper examines the broader implications of this trend on how the term “undocumented” is defined, as well as the advocacy and policy implications such new statuses portend. Having the world's largest undocumented population, the U.S. case can also shed light on our broader understanding of the undocumented label as a globally-referenced category.